Metrological support for quantities and units in digital systems. (December 2021) - Hall, B.D.; Kuster, M.
Abstract: Unit systems and dimensions emerged in the late 19th century. However, efforts to adapt these ideas for use in modern digital systems are proving a challenge. We provide an interpretation of units and dimensions that clarifies the main reasons for difficulties. We then suggest how a digital system would provide adequate support for quantities and units. A layer of metrological information is envisaged that would track details and allow familiar unit formats to be rendered. Three independent aspects of the data should be captured: 1) the quantity; 2) the measurement scale, scale type and conversion functions; and 3) the semantics of numerical data.